Recovery in soccer: Part I - Post-match fatigue and time course of recovery - Nedelec, M.; McCall, A.; Carling, C.; Legall, F.; Berthoin, S.; Dupont, G. (Sports Medicine, 2012)
In elite soccer, players are frequently required to play consecutive matches interspersed by 3 days and complete physical performance recovery may not be achieved. Incomplete recovery might result in underperformance and injury. During congested schedules, recovery strategies are therefore required to alleviate post-match fatigue, regain performance faster and reduce the risk of injury. This article is Part I of a subsequent companion review and deals with post-match fatigue mechanisms and recovery kinetics of physical performance (sprints, jumps, maximal strength and technical skills), cognitive, subjective and biochemical markers. The companion review will analyse recovery strategies used in contemporary professional soccer. Soccer involves many physically demanding activities including sprinting, changes in running speed, changes of direction, jumps and tackles, as well as technical actions such as dribbling, shooting and passing. These activities lead to a post-match fatigue that is linked to a combination of dehydration, glycogen depletion, muscle damage and mental fatigue. The magnitude of soccer match-induced fatigue, extrinsic factors (i.e. match result, quality of the opponent, match location, playing surface) and/or intrinsic factors (i.e. training status, age, gender, muscle fibre typology), potentially influence the time course of recovery. Recovery in soccer is a complex issue, reinforcing the need for future research to estimate the quantitative importance of fatigue mechanisms and identify influencing factors. Efficient and individualized recovery strategies may consequently be proposed.